Gravity (JOURNAL OF ADVANCES IN PHYSICS, 2017)
Considering two balls of Z protons each near each other the residual electric potential V is calculated. Also the gravitational potential is calculated. The Gravitational constant is the same for both. Thus the electric field creates gravity. This calculation is possible because the multibody energy states are known exactly. The relativistic correction of 2 has been found from the Klein-Gordon Equation solution. This finding is an important step in reducing known forces to one field. Recall the electric field is generated by motion in the magnetic field of atoms of a magnetic dipole. The mass is a function of the length of the magnetic dipole.